DESCRIPTION OF KNOWLEDGE OF WOMEN OF RELIABLE AGE ABOUT CERVIC CANCER IN SUB-DISTRICT BALANDETE IN WORK AREA KOLAKA HEALTH CENTER YEAR 2021 - Hernah Riana (Homes Journal = Hospital Management Studies Journal, 2021)
Background:Cervical cancer is a malignant tumor that grows in the cervix, which is the lowest part of the uterus attached to the top of the vagina, usually cervical cancer attacks women aged 35-55 years.Objective:This study aims to find out the description of the knowledge of women of childbearing age about cervical cancer based on their occupation and sources of information in the Balandete village, the working area of the Kolaka Public Health Center 2021.Method: The research design used was cross sectional. The population in this study amounted to 215 respondents. The sampling technique used was accidental sampling and obtained a sample of 68 respondents. The data colcleted in this study were data on education, employment and information resourcesdescribe to describe or provide an overview of women's knowledge about cervical cancer in the village of Balandete, the working area of the Kolaka Public Health Center 2021.Result: The results WUS knowledge about cervical cancer is known that out of 68 respondents (100%) who have good knowledge, 17 respondents (25%), have sufficient knowledge, 41 respondents (60.3%) and 10 respondents (14.7%) have less knowledge.Conclusion:in Based on the results of research that has been carried out in the Balandete Village in the Kolaka Community Health Center work area in 2021about the knowledge of women of childbearing age about cervical cancer in the Balandete Village based on education, occupation, and sources of information, the results of research on cervical cancer are quite good but need to be improved again so that the mother's knowledge about cervical cancer it's better than now.